GF / TiB2 / TiO2-based super-hydrophobic composite coating and preparation method thereof

Through the preparation of GF/TiB2/TiO2-based superhydrophobic composite coating, the use of mesh crosslinking structure and micro-nano-scale rough structure, the existing superhydrophobic coating has been solved. The corrosion resistance and mechanical durability of the existing superhydrophobic coating under harsh working conditions is insufficient. Problem, good corrosion resistance, self-cleaning and multi-matrix universality are achieved, reducing production costs.

CN119264798APending Publication Date: 2025-01-07XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411511606.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing superhydrophobic coatings have poor corrosion resistance under harsh working conditions, insufficient mechanical durability, complex preparation process and high cost, and some processes use toxic chemicals, which limits their industrial applications.

Method used

The preparation method of GF/TiB2/TiO2-based superhydrophobic composite coating is adopted, and the polydimethylsiloxane modifier, polyurethane binder, glass fiber powder, TiB2 powder, TiO2 powder and ethyl acetate solvent are mixed to form The suspension is uniform and the curing agent is added and sprayed to form a coating, using the mesh crosslinking structure and the micro-nano-scale rough structure to enhance superhydrophobicity and mechanical stability.

Benefits of technology

It achieves good corrosion resistance, self-cleaning and soil resistance under harsh working conditions, has universality of multiple substrates and low production costs, extends the service life of the coating, and improves the mechanical stability of the coating and wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264798A_ABST
    Figure CN119264798A_ABST
Patent Text Reader

Abstract

The invention discloses a GF / TiB2 / TiO2-based super-hydrophobic composite coating and a preparation method thereof.The preparation method comprises the steps that a polydimethylsiloxane modifier, a polyurethane binder, glass fiber powder, TiB2 powder and TiO2 powder are added into an ethyl acetate solvent, and uniform suspension liquid is obtained after sufficient stirring; adding a curing agent of a polydimethylsiloxane modifier into the suspension, fully stirring, and uniformly mixing to obtain the super-hydrophobic composite coating. And uniformly spraying the super-hydrophobic composite coating on a substrate material with a clean surface, and curing to obtain the GF / TiB2 / TiO2-based super-hydrophobic composite coating. The adhesive can adapt to different types of base materials, has good flexibility and can deform along with tiny deformation of the base materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrophobic materials, and in particular relates to a GF / TiB2 / TiO2-based super-hydrophobic composite coating and a preparation method thereof. Background Art

[0002] Superhydrophobic materials have a significant hydrophobic effect due to their surface liquid contact angle greater than 150° and rolling angle less than 10°. They can effectively reduce the adhesion between water droplets and objects and have self-cleaning, anti-fouling, anti-icing, and anti-corrosion functions. Superhydrophobicity is the result of the synergistic effect of surface micro-nanostructures and low surface energy substances, and is derived from the "lotus effect" in nature. Based on the many functional properties of superhydrophobic materials, different types of superhydrophobic coatings have been developed in recent years, and have shown important application prospects in the fields of construction, transportation, electronics, textiles, and biomedicine.

[0003] Existing super-hydrophobic coatings face many limitations. Because the microstructure on its surface is easily damaged by external friction or impact, the mechanical durability of the coating is poor, and the preparation process is complicated and costly. In addition, some preparation processes involve toxic chemicals, which are environmentally friendly and limit their wide application in industry. Composite super-hydrophobic coatings have become a research focus. By combining different types of materials, the mechanical properties of the coating can be improved, and its long-term stable super-hydrophobicity can be guaranteed. For example, a composite coating combining inorganic nanoparticles and organic polymer materials can improve its wear resistance and chemical stability, and significantly extend the service life of the coating. This type of composite coating has good environmental adaptability and can maintain its super-hydrophobic properties under different temperature, humidity, acid and alkali environments.

[0004] At present, in order to expand the application field of superhydrophobic coatings, there is an urgent need for a corrosion-resistant superhydrophobic composite coating with excellent self-cleaning, anti-fouling, mechanical stability, multi-substrate universality and low cost. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a GF / TiB2 / TiO2-based super-hydrophobic composite coating and a preparation method thereof in view of the deficiencies in the above-mentioned prior art, so that the super-hydrophobic coating has good long-term anti-corrosion effect under harsh working conditions, and is used to solve the technical problem that the existing super-hydrophobic coating has poor long-term anti-corrosion effect.

[0006] The present invention adopts the following technical solutions: A method for preparing a GF / TiB2 / TiO2-based super-hydrophobic composite coating comprises the following steps: S1, adding polydimethylsiloxane modifier, polyurethane binder, glass fiber powder, TiB2 powder and TiO2 powder into ethyl acetate solvent, and stirring thoroughly to obtain a uniform suspension; S2, adding a curing agent of a polydimethylsiloxane modifier to the suspension obtained in step S1, stirring the mixture sufficiently to obtain a super-hydrophobic composite coating; S3. Spray the super-hydrophobic composite coating evenly on the clean surface of the substrate material, and obtain the GF / TiB2 / TiO2-based super-hydrophobic composite coating after curing.

[0007] Preferably, in step S1, the particle size of the glass fiber powder is 5-15 μm; the particle size of the TiB2 powder is 1-3 μm; and the particle size of the TiO2 powder is 23-28 nm.

[0008] Preferably, in step S1, the mass ratio of the polydimethylsiloxane modifier to the ethyl acetate solvent is (5-6):200; the mass ratio of the polyurethane binder to the ethyl acetate solvent is (2.5-3):200.

[0009] Preferably, the mass ratio of glass fiber powder to ethyl acetate solvent is (0.1-0.12):180.

[0010] Preferably, the mass ratio of TiB2 powder to ethyl acetate solvent is (8~8.5):180.

[0011] Preferably, the mass ratio of TiO2 powder to ethyl acetate solvent is (1-1.2):180.

[0012] Preferably, in step S2, the mass ratio of the curing agent of the polydimethylsiloxane modifier to the polydimethylsiloxane modifier is 1-1.2:10.

[0013] Preferably, in step S3, the nozzle diameter used for spraying is 1.0-1.5 mm, the pressure is 0.6-0.7 MPa, and the distance is 10-15 cm.

[0014] Preferably, in step S3, curing is performed at 60° C. for 1 to 2 hours to obtain a GF / TiB2 / TiO2-based super-hydrophobic composite coating.

[0015] Another technical solution of the present invention is that the GF / TiB2 / TiO2-based super-hydrophobic composite coating has a contact angle of 159.50°±1.00°~163.21°±3.49° and a rolling angle of 5.75°±0.90°~30.8°±2.19°.

[0016] Compared with the prior art, the present invention has at least the following beneficial effects: A method for preparing a GF / TiB2 / TiO2-based super-hydrophobic composite coating comprises the following steps: using micron-sized GF powder and TiB2 powder as micro-skeleton and anti-wear bearing particles respectively, using nano-sized TiO2 powder as reinforcing particles, using a curing agent of a polydimethylsiloxane modifier to promote the curing of the polydimethylsiloxane modifier, and coating the cured polydimethylsiloxane modifier and polyurethane binder on the GF powder, TiB2 powder and TiO2 powder to form a network cross-linked structure; the micron-sized GF / TiB2 powder and nano-sized TiO2 powder construct a micro-nano rough structure, and the surface energy of the polydimethylsiloxane modifier is relatively low, thereby obtaining Super hydrophobicity; due to its super hydrophobicity, it has good self-cleaning ability and anti-pollution ability; since the super hydrophobic composite coating has good corrosion resistance and forms effective protection for the base material, the network cross-linked structure formed by the polydimethylsiloxane modifier and the polyurethane binder can absorb the stress, and the micron-sized TiB2 powder serves as a micro-skeleton and anti-wear load-bearing particles, so the coating is not easy to fall off and has good mechanical stability; the network cross-linked structure formed by the polydimethylsiloxane modifier and the polyurethane binder has good adhesion and can adapt to different types of substrates. At the same time, it has good flexibility and can deform simultaneously with the slight deformation of the substrate.

[0017] Furthermore, the particle size of the glass fiber powder is set at 5~15μm, which can provide good mechanical strength and toughness for the coating; the moderate particle size helps to enhance the impact resistance and wear resistance of the coating, so that it can maintain stable performance under long-term friction or external force. The larger particle size of the glass fiber powder can form mechanical support in the coating, increase the overall strength and stability of the coating, and prevent the coating from cracking or peeling due to stress concentration. The particle size range of TiB2 powder is 1~3μm, which can provide excellent wear resistance and hardness for the coating. TiB2 is a hard material, and its micron-sized particles can be embedded in the coating, which plays a role in wear resistance and enhancing the hardness of the coating, extending the service life of the coating. The appropriate particle size can form a uniform microscopic rough structure on the surface of the coating, which is very important for achieving superhydrophobicity. Too large a particle size will affect the flatness of the surface, and too small a particle size will not provide sufficient mechanical support and roughness. The TiB2 particle size of 1~3μm can effectively improve the wear resistance and hydrophobicity of the surface. The particle size of TiO2 powder is set to nanoscale (23-28nm), and its main purpose is to provide nanoscale surface roughness for the coating. Such micro-nanostructure can significantly reduce the contact area between water droplets and the coating surface through the Cassie-Baxter effect, thereby enhancing the superhydrophobic properties of the coating.

[0018] Further, polydimethylsiloxane has very low surface energy, so it is a key component to improve the super-hydrophobic performance of the coating. Its addition can significantly improve the hydrophobicity of the coating surface, thereby achieving a higher water contact angle and rolling angle, and has good flexibility, and can give the coating higher elasticity and deformation resistance. When subjected to mechanical stress, the coating can maintain integrity to prevent cracks or peeling. Polyurethane binders are mainly used to enhance the adhesion between the coating and the substrate, ensuring that the coating can be firmly attached to the surface of various substrates. In addition, polyurethane itself has good mechanical properties, particularly wear resistance and corrosion resistance. By using polyurethane binders reasonably, the wear resistance of the coating can be improved and the service life of the coating can be extended. By reasonably setting the mass ratio of the three, the coating can achieve ideal super-hydrophobic performance and mechanical stability.

[0019] Furthermore, the mass ratio of glass fiber powder to ethyl acetate solvent can ensure that the glass fiber is evenly distributed in the coating, enhance the mechanical properties of the coating, optimize the coating performance, and ensure that the coating has a good film-forming effect. Through reasonable ratio control, the coating can achieve higher wear resistance, strength and durability.

[0020] Furthermore, TiB2 powder has high hardness and wear resistance, but due to its high density, it is easy to settle or agglomerate. Through the appropriate mass ratio of TiB2 to ethyl acetate, it is possible to ensure that TiB2 is evenly dispersed in the coating to form a stable suspension, and to avoid precipitation or aggregation of the powder in the mixture, thereby ensuring the uniformity and performance consistency of the coating. TiB2 is a superhard material that can significantly improve the wear resistance and impact resistance of the coating. By adding an appropriate amount of TiB2 powder, the coating can be given a higher mechanical strength. A reasonable mass ratio can ensure that the TiB2 particles are embedded in the coating matrix, enhancing the wear resistance of the coating without excessively affecting the fluidity and film-forming properties of the coating.

[0021] Further, due to the particle size of TiO2 powder is usually at nanometer level, it is easy to reunite, so the mass ratio of reasonable TiO2 and ethyl acetate helps to improve its dispersibility. Appropriate ethyl acetate can help TiO2 powder to form a uniform suspension in coating, prevent particles from agglomerating or settling, and ensure that it is evenly distributed in the coating. Nano-scale TiO2 powder can form nanostructures on the coating surface, and the ratio of reasonable TiO2 and ethyl acetate can ensure the stability and consistency of these nanostructures, maximize the hydrophobicity of the coating. Tiny TiO2 particles can fill the coating surface, improve the roughness of the surface, reduce the contact area between water droplets and the surface, thereby improving the contact angle and enhancing the hydrophobic effect. In addition, the pressure, nozzle diameter and spraying distance of spraying determine the formation of micro-nanostructure on the coating surface, which is crucial for super-hydrophobic performance. Reasonable spraying parameters help to form a consistent roughness, reduce the contact area between water droplets and the coating surface, thereby improving the water contact angle and the sliding angle, and enhancing the super-hydrophobic effect.

[0022] Furthermore, the curing of polydimethylsiloxane is completed by the chemical reaction between the curing agent and the polydimethylsiloxane modifier. A reasonable mass ratio ensures that the curing agent and polydimethylsiloxane react fully to form a stable cross-linked structure. Too little curing agent may lead to incomplete reaction, and the mechanical properties and durability of the coating will decrease; too much curing agent may increase the brittleness of the material.

[0023] Furthermore, setting the appropriate spray pressure, nozzle diameter and spray distance can ensure that the coating is evenly covered on the substrate surface. Proper control of spray parameters can avoid problems such as uneven coating thickness, accumulation or gaps, and ensure that the coating has uniform thickness and performance.

[0024] Furthermore, the setting of curing parameters (temperature and time) ensures that the chemical reaction between the polymer and the curing agent in the coating is fully carried out. Appropriate curing time and temperature can ensure the completeness of the cross-linking reaction, form a strong three-dimensional network structure, and improve the mechanical properties and durability of the coating. Insufficient curing time or too low temperature may lead to incomplete curing of the coating, thereby affecting its mechanical stability.

[0025] In summary, the GF / TiB2 / TiO2-based super-hydrophobic composite coating prepared by the present invention has good self-cleaning, anti-fouling, corrosion resistance, mechanical stability, and multi-substrate universality.

[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings to be used in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 The contact angle and rolling angle variation curves of the coatings prepared in Examples 1, 2, 3, 4, 5, 6, 7 and 8; Figure 2 Scanning electron micrographs of the coatings prepared in Examples 1, 2, 3, 4, 5, 6, 7 and 8; Figure 3 Bode plots and polarization curves of a GF / TiB2 / TiO2-based super-hydrophobic composite coating prepared in Example 6 and a comparative test of the corrosion resistance of the prepared super-hydrophobic coating and an AA3003 aluminum plate substrate. DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.

[0031] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.

[0032] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.

[0033] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.

[0034] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6-22" represents that all real numbers between "6-22" are listed in this document, and "6-22" is just an abbreviation of these numerical combinations.

[0035] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.

[0036] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0037] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.

[0038] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.

[0039] The present invention discloses a method for preparing a GF / TiB2 / TiO2-based super-hydrophobic composite coating, comprising the following steps: S1. Add polydimethylsiloxane modifier, polyurethane binder, glass fiber (GF) powder, TiB2 powder and TiO2 powder into ethyl acetate solvent and stir thoroughly to obtain a uniform suspension; Among them, the particle size of GF powder is 5~15μm; the particle size of TiB2 powder is 1~3μm; and the particle size of TiO2 powder is 23~28nm.

[0040] The mass ratio of polydimethylsiloxane modifier to ethyl acetate solvent is (5~6):200.

[0041] The mass ratio of the polyurethane binder to the ethyl acetate solvent is (2.5~3):200.

[0042] Among them, the mass ratio of GF powder to ethyl acetate solvent is (0.1~0.12):180; the mass ratio of TiB2 powder to ethyl acetate solvent is (8~8.5):180; the mass ratio of TiO2 powder to ethyl acetate solvent is (1~1.2):180.

[0043] S2, adding a curing agent of a polydimethylsiloxane modifier to the suspension obtained in step S1, stirring the mixture sufficiently to obtain a super-hydrophobic composite coating; The mass ratio of the curing agent of the polydimethylsiloxane modifier to the polydimethylsiloxane modifier is (1~1.2):10.

[0044] S3. Spray the super-hydrophobic composite coating evenly on the substrate material with a clean surface and no foreign matter, and cure it at a temperature of 60-70°C for 1-2 hours.

[0045] The GF / TiB2 / TiO2-based super-hydrophobic composite coating prepared by the method of the present invention has a contact angle generally greater than 150°, ranging from 155° to 165°; a rolling angle generally less than 7°, ranging from 3° to 6°; a corrosion resistance efficiency greater than 95% in a corrosive medium (such as a 3.5 wt.% NaCl solution); after being covered with pollutants (such as soil, dust, etc.), the pollutant removal rate can reach more than 98% after being treated with water droplet rolling; after being immersed in pollutants for a period of time, the surface contamination rate is generally less than 7%; it has multi-substrate universality and can adapt to a variety of different substrates.

[0046] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0047] Example 1 Step 1: First, add 0.5g of polydimethylsiloxane modifier, 0.25g of polyurethane binder, 0.01g of GF powder with a particle size of 5μm, and 0.8g of TiB2 powder with a particle size of 1μm into 18g of ethyl acetate solvent, and stir thoroughly to obtain a uniform suspension; Step 2: Add 0.05 g of a polydimethylsiloxane modifier curing agent to the suspension obtained in step 1, stir thoroughly to mix evenly, and obtain a super-hydrophobic composite coating; Step 3: Use a spray gun with a nozzle diameter of 1.5 mm, spray the super-hydrophobic composite coating evenly on a clean AA3003 aluminum plate with no foreign matter at a distance of 10 cm under a pressure of 0.6 MPa, and cure it at 60°C for 1.5 hours to obtain an AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface.

[0048] Example 2 Step 1: first add 0.5g of polydimethylsiloxane modifier, 0.25g of polyurethane binder, 0.01g of GF powder with a particle size of 5μm, 0.8g of TiB2 powder with a particle size of 1μm, and 0.06g of TiO2 powder with a particle size of 23nm into 18g of ethyl acetate solvent, and stir thoroughly to obtain a uniform suspension; Step 2: Add 0.05 g of a polydimethylsiloxane modifier curing agent to the suspension obtained in step 1, stir thoroughly to mix evenly, and obtain a super-hydrophobic composite coating; Step 3: Use a spray gun with a nozzle diameter of 1.5 mm, at a pressure of 0.6 MPa and a distance of 10 cm, to evenly spray the super-hydrophobic composite coating on a clean AA3003 aluminum plate with no foreign matter on the surface, and cure it at 60°C for 1.5 hours to obtain an AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface.

[0049] Example 3 Step 1: First, add 0.5g of polydimethylsiloxane modifier, 0.25g of polyurethane binder, 0.01g of GF powder with a particle size of 5μm, 0.8g of TiB2 powder with a particle size of 1μm, and 0.07g of TiO2 powder with a particle size of 23nm into 18g of ethyl acetate solvent, and stir thoroughly to obtain a uniform suspension; Step 2: Add 0.05 g of a polydimethylsiloxane modifier curing agent to the suspension obtained in step 1, stir thoroughly to mix evenly, and obtain a super-hydrophobic composite coating; Step 3: Use a spray gun with a nozzle diameter of 1.5 mm, spray the super-hydrophobic composite coating evenly on a clean AA3003 aluminum plate with no foreign matter at a distance of 10 cm under a pressure of 0.6 MPa, and cure it at 60°C for 1.5 hours to obtain an AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface.

[0050] Example 4 Step 1: first add 0.5g of polydimethylsiloxane modifier, 0.25g of polyurethane binder, 0.01g of GF powder with a particle size of 5μm, 0.8g of TiB2 powder with a particle size of 1μm, and 0.08g of TiO2 powder with a particle size of 23nm into 18g of ethyl acetate solvent, and stir thoroughly to obtain a uniform suspension; Step 2: Add 0.05 g of a polydimethylsiloxane modifier curing agent to the suspension obtained in step 1, stir thoroughly to mix evenly, and obtain a super-hydrophobic composite coating; Step 3: Use a spray gun with a nozzle diameter of 1.5 mm, at a pressure of 0.6 MPa and a distance of 10 cm, to evenly spray the super-hydrophobic composite coating on a clean AA3003 aluminum plate with no foreign matter on the surface, and cure it at 60°C for 1.5 hours to obtain an AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface.

[0051] Example 5 Step 1: First, add 0.5g of polydimethylsiloxane modifier, 0.25g of polyurethane binder, 0.01g of GF powder with a particle size of 5μm, 0.8g of TiB2 powder with a particle size of 1μm, and 0.09g of TiO2 powder with a particle size of 23nm into 18g of ethyl acetate solvent, and stir thoroughly to obtain a uniform suspension; Step 2: Add 0.05 g of a polydimethylsiloxane modifier curing agent to the suspension obtained in step 1, stir thoroughly to mix evenly, and obtain a super-hydrophobic composite coating; Step 3: Use a spray gun with a nozzle diameter of 1.5 mm, at a pressure of 0.6 MPa and a distance of 10 cm, to evenly spray the super-hydrophobic composite coating on a clean AA3003 aluminum plate with no foreign matter on the surface, and cure it at 60°C for 1.5 hours to obtain an AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface.

[0052] Example 6 Step 1: First, add 0.5g of polydimethylsiloxane modifier, 0.25g of polyurethane binder, 0.01g of GF powder with a particle size of 5μm, 0.8g of TiB2 powder with a particle size of 1μm, and 0.10g of TiO2 powder with a particle size of 23nm into 18g of ethyl acetate solvent, and stir thoroughly to obtain a uniform suspension; Step 2: Add 0.05 g of a polydimethylsiloxane modifier curing agent to the suspension obtained in step 1, stir thoroughly to mix evenly, and obtain a super-hydrophobic composite coating; Step 3: Use a spray gun with a nozzle diameter of 1.5 mm, at a pressure of 0.6 MPa and a distance of 10 cm, to evenly spray the super-hydrophobic composite coating on a clean AA3003 aluminum plate with no foreign matter on the surface, and cure it at 60°C for 1.5 hours to obtain an AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface.

[0053] Example 7 Step 1: First, add 0.5g of polydimethylsiloxane modifier, 0.25g of polyurethane binder, 0.01g of GF powder with a particle size of 5μm, 0.8g of TiB2 powder with a particle size of 1μm, and 0.11g of TiO2 powder with a particle size of 23nm into 18g of ethyl acetate solvent, and stir thoroughly to obtain a uniform suspension; Step 2: Add 0.05 g of a polydimethylsiloxane modifier curing agent to the suspension obtained in step 1, stir thoroughly to mix evenly, and obtain a super-hydrophobic composite coating; Step 3: Use a spray gun with a nozzle diameter of 1.5 mm, at a pressure of 0.6 MPa and a distance of 10 cm, to evenly spray the super-hydrophobic composite coating on a clean AA3003 aluminum plate with no foreign matter on the surface, and cure it at 60°C for 1.5 hours to obtain an AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface.

[0054] Example 8 Step 1: First, add 0.5g of polydimethylsiloxane modifier, 0.25g of polyurethane binder, 0.01g of GF powder with a particle size of 5μm, 0.8g of TiB2 powder with a particle size of 1μm, and 0.12g of TiO2 powder with a particle size of 23nm into 18g of ethyl acetate solvent, and stir thoroughly to obtain a uniform suspension; Step 2: Add 0.05 g of a polydimethylsiloxane modifier curing agent to the suspension obtained in step 1, stir thoroughly to mix evenly, and obtain a super-hydrophobic composite coating; Step 3: Use a spray gun with a nozzle diameter of 1.5 mm, at a pressure of 0.6 MPa and a distance of 10 cm, to evenly spray the super-hydrophobic composite coating on a clean AA3003 aluminum plate with no foreign matter on the surface, and cure it at 60°C for 1.5 hours to obtain an AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface.

[0055] Example 9 Step 1: first add 0.45g of polydimethylsiloxane modifier, 0.225g of polyurethane binder, 0.012g of GF powder with a particle size of 15μm, 0.85g of TiB2 powder with a particle size of 3μm, and 0.12g of TiO2 powder with a particle size of 28nm into 18g of ethyl acetate solvent, and stir thoroughly to obtain a uniform suspension; Step 2: Add 0.054 g of a curing agent of a polydimethylsiloxane modifier to the suspension obtained in step 1, stir thoroughly to mix evenly, and obtain a super-hydrophobic composite coating; Step 3: Use a spray gun with a nozzle diameter of 1.0 mm, spray the super-hydrophobic composite coating evenly on a clean AA3003 aluminum plate with no foreign matter at a distance of 15 cm under a pressure of 0.7 MPa, and cure it at 70°C for 2 hours to obtain an AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface.

[0056] Example 10 Step 1: first add 0.54g of polydimethylsiloxane modifier, 0.27g of polyurethane binder, 0.012g of GF powder with a particle size of 15μm, 0.85g of TiB2 powder with a particle size of 3μm, and 0.12g of TiO2 powder with a particle size of 28nm into 18g of ethyl acetate solvent, and stir thoroughly to obtain a uniform suspension; Step 2: Add 0.054 g of a curing agent of a polydimethylsiloxane modifier to the suspension obtained in step 1, stir thoroughly to mix evenly, and obtain a super-hydrophobic composite coating; Step 3: Use a spray gun with a nozzle diameter of 1.0 mm, spray the super-hydrophobic composite coating evenly on a clean AA3003 aluminum plate with no foreign matter at a distance of 15 cm under a pressure of 0.7 MPa, and cure it at 70°C for 2 hours to obtain an AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface.

[0057] The coatings prepared in Examples 1 to 8 were respectively measured for contact angle and rolling angle using a contact angle measuring instrument. The contact angle and rolling angle values ​​are shown in FIG. Figure 1 As shown in the figure, it can be seen that the super-hydrophobic coating prepared in Example 6 has the best super-hydrophobicity, with a contact angle of 163.21°±3.49° and a rolling angle of 5.75°±0.90°; the contact angle of the coating obtained in Example 1 is 159.50°±1.00°, and the rolling angle is 30.8°±2.19°; The coatings prepared in Examples 1 to 8 were subjected to surface morphology analysis. Figure 2 As shown in the figure, it can be found that the super hydrophobic coating has a micro-nano structure with GF weaving and micro-nano multi-level ceramic particles, which enables it to produce an air cushion layer in the solution, thus having good corrosion resistance.

[0058] The following is a comparative test between the AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface and the ordinary AA3003 aluminum plate: 1. Comparison of hydrophobicity: The contact angle and rolling angle of the AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface and the ordinary AA3003 aluminum plate were measured using a contact angle meter. The contact angle of the AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface was 163.21°±3.49°, and the rolling angle was 5.75°±0.90°. The contact angle of the ordinary AA3003 aluminum plate was 74.6°±3.7°, and the rolling angle was greater than 90°. 2. Comparison of self-cleaning ability: 1g of standard sand was sprinkled at an inclination angle of 10° on the exposed surface of the AA3003 aluminum plate with the super-hydrophobic composite coating and the ordinary AA3003 aluminum plate. Then, water droplets were dripped from 5cm above the sample. The dripping water droplets can take away the sand on the surface. After measurement, only 300μL of water is needed to take away the sand on the surface of the AA3003 aluminum plate with the super-hydrophobic composite coating, while the sand on the ordinary AA3003 aluminum plate requires 7250μL of water to take away.

[0059] 3. Comparison of anti-pollution ability: The AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface and the ordinary AA3003 aluminum plate were immersed in milk, cola and orange juice at the same time. After 24 hours, the proportion of the surface contaminated area to the total area was compared. After immersion in milk for 24 hours, the contaminated area of ​​the AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface was 0%, and the contaminated area of ​​the ordinary AA3003 aluminum plate was 99%. After immersion in cola for 24 hours, the contaminated area of ​​the AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface was 0%, and the contaminated area of ​​the ordinary AA3003 aluminum plate was 95%. After immersion in orange juice for 24 hours, the contaminated area of ​​the AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface was 0%, and the contaminated area of ​​the ordinary AA3003 aluminum plate was 87%.

[0060] 4. Corrosion resistance comparison: The corrosion resistance of the AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface is compared with that of the ordinary AA3003 aluminum plate. In a standard three-electrode system, the exposed area is 1cm 2 The samples were used as working electrodes, saturated calomel electrode (SCE) as reference electrode, and platinum sheet as counter electrode. All samples were immersed in 3.5wt.% NaCl solution for 30min to reach a stable open circuit potential ( E OCP ), and then electrochemical impedance spectroscopy (EIS) and polarization tests were performed. EIS measurements were performed in the frequency range of 100kHz-0.01Hz by applying a 10mV sinusoidal perturbation, as shown in Figure 3 As shown, the low frequency of the AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface | Z | 0.01 Hz 2.9×10 5 Ω·cm 2 , low frequency of ordinary AA3003 aluminum plate | Z | 0.01 Hz 4.6×10 3 Ω·cm 2 , the difference between the two is 2 orders of magnitude, indicating that the super-hydrophobic coating has excellent corrosion resistance; At -0.3V SCE ~0.3V SCE and E OCP Potentiodynamic polarization (PDP) was performed at a scan rate of 0.2 mV / s within the potential range, and the polarization curves were fitted using the Tafel extrapolation method, such as Figure 3 As shown in Figure 2, the corrosion current density of the AA3003 aluminum plate with the super-hydrophobic composite coating on its surface is 5.93×10 -8 A.cm -2 The corrosion current density of ordinary AA3003 aluminum plate is 1.31×10 -6A.cm -2 The difference between the two is 2 orders of magnitude. The corrosion potential of the AA3003 aluminum plate with the super-hydrophobic composite coating attached to the surface is -0.65V, and the corrosion current potential of the ordinary AA3003 aluminum plate is -0.73V, indicating that the super-hydrophobic coating has a low corrosion rate and outstanding anti-corrosion properties.

[0061] The super hydrophobic composite coating of the present invention is subjected to mechanical stability test and multi-substrate universality test: 1. Mechanical stability test: Superhydrophobic materials usually have a unique micro-nano rough structure and are easily damaged under external forces. Therefore, the mechanical stability of artificial superhydrophobic coatings is an important indicator that determines their wide application. In order to evaluate the mechanical robustness of the coating, a sandpaper wear test was carried out. The AA3003 aluminum plate with the superhydrophobic composite coating attached to the surface was placed face down on sandpaper (2000 mesh), and then rubbed on the sandpaper at a constant speed of 5 mm / s. The calculated pressure was 1.33 kPa, and a linear reciprocating distance of 10 cm (total distance of 20 cm) was defined as a friction cycle. After several cycles of wear, the corresponding contact angle and rolling angle of the coating sample were measured after each friction cycle to evaluate the changes in the wettability and mechanical stability of the coating. After a 400 cm sandpaper wear test, the WCA of the coating was 156.90°±2.61°, the SA was 10.00°±0.50°, and the hydrophobicity did not change much.

[0062] Table 1 Contact angles of super-hydrophobic composite coatings sprayed on different substrate surfaces

[0063] 2. Multi-substrate universality test: The universality of multi-substrates was evaluated by testing the surface wettability of the superhydrophobic composite coating on wood chips, plastics, filter paper, sandpaper and glass slides. After measurement, each sample showed superhydrophobicity. The specific contact angle values ​​are shown in Table 1.

[0064] In summary, a GF / TiB2 / TiO2-based super-hydrophobic composite coating and preparation method thereof of the present invention only require that a specific proportion of polydimethylsiloxane modifier, polyurethane binder, GF powder, TiB2 powder, and TiO2 powder be put into an ethyl acetate solvent and stirred, and then a certain amount of a curing agent of the polydimethylsiloxane modifier be put into the solvent, and the super-hydrophobic composite coating of the present invention can be obtained after sufficient stirring to make it mix uniformly, and the process is simple and cost-effective.

[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a GF / TiB2 / TiO2-based super-hydrophobic composite coating, characterized in that: The following steps are involved: S1, adding polydimethylsiloxane modifier, polyurethane binder, glass fiber powder, TiB2 powder and TiO2 powder into ethyl acetate solvent, and stirring thoroughly to obtain a uniform suspension; S2, adding a curing agent of a polydimethylsiloxane modifier to the suspension obtained in step S1, stirring the mixture sufficiently to obtain a super-hydrophobic composite coating; S3. Spray the super-hydrophobic composite coating evenly on the clean surface of the substrate material, and obtain the GF / TiB2 / TiO2-based super-hydrophobic composite coating after curing.

2. The GF / TiB2 / TiO2-based super-hydrophobic composite coating preparation method according to claim 1, characterized in that: In step S1, the particle size of the glass fiber powder is 5-15 μm; the particle size of the TiB2 powder is 1-3 μm; and the particle size of the TiO2 powder is 23-28 nm.

3. The GF / TiB2 / TiO2-based super-hydrophobic composite coating preparation method according to claim 1, characterized in that, In step S1, the mass ratio of the polydimethylsiloxane modifier to the ethyl acetate solvent is (5-6):200; the mass ratio of the polyurethane binder to the ethyl acetate solvent is (2.5-3):

200.

4. The GF / TiB2 / TiO2-based super-hydrophobic composite coating preparation method according to claim 3, characterized in that, The mass ratio of glass fiber powder to ethyl acetate solvent is (0.1~0.12):

180.

5. The GF / TiB2 / TiO2-based super-hydrophobic composite coating preparation method according to claim 3, characterized in that, The mass ratio of TiB2 powder to ethyl acetate solvent is (8~8.5):

180.

6. The method for preparing a GF / TiB2 / TiO2-based super-hydrophobic composite coating according to claim 3, wherein: The mass ratio of TiO2 powder to ethyl acetate solvent is (1~1.2):

180.

7. The method for preparing a GF / TiB2 / TiO2-based super-hydrophobic composite coating according to claim 1, wherein: In step S2, the mass ratio of the curing agent of the polydimethylsiloxane modifier to the polydimethylsiloxane modifier is (1-1.2):

10.

8. The method for preparing a GF / TiB2 / TiO2-based super-hydrophobic composite coating according to claim 1, wherein: In step S3, the nozzle diameter used for spraying is 1.0-1.5 mm, the pressure is 0.6-0.7 MPa, and the distance is 10-15 cm.

9. The method for preparing a GF / TiB2 / TiO2-based super-hydrophobic composite coating according to claim 1, wherein: In step S3, the GF / TiB2 / TiO2-based super-hydrophobic composite coating is obtained by curing at 60°C for 1-2 hours.

10. A GF / TiB2 / TiO2-based super-hydrophobic composite coating prepared according to the method of any one of claims 1 to 9, characterized in that: The contact angle is 159.50°±1.00°~163.21°±3.49°, and the rolling angle is 5.75°±0.90°~30.8°±2.19°.